Distribusi Frekuensi Beberapa Subtipe Human Immunodeficiency Virus-1 (HIV-1) di Provinsi Kalimantan Barat Tahun 2010 - -, Roselinda (Central Basic Biomedical and Health Technology, 2013)
HIV-1 subtype distribution in the province of West Kalimantan with a sufficient amount of data has not been so well known, so is the predominant subtype and proportion. The purpose of the analysis is to look at distribution of HIV-1 subtypes circulating in West Kalimantan province with risk factors. The data analyzed came from surveys of HIV-1 virus genotypes in West Kalimantan in 2010 in the case of HIV/AIDS chosen purposively who visited the clinic Voluntary Care and Treatment (VCT) in Pontianak and Singkawang. For each city chosen purposively 1 hospital. Blood specimens were taken from patients to be examined by PCR and sequencing, then the data sociodemographic and medical history interview was conducted with a structured questionnaire after obtaining consent from the patient of the 80 serum specimens examined by PCR and sequencing subtype CRF01_AE obtained by 83.4%. Also found subtype E of 10.4%, AC subtypes, A and C, respectively 2.1% . Highest proportion of subtype CRF01_AE was found in the group that has the status of a widow/not married, the group with the Malays and the age group 15-30 years. Most transmission through IDU history. HIV-1 subtype CRF01_AE is predominant subtype recombinant circulating in the province of West Kalimantan.Keywords: HIV-1 subtypes, West Kalimantan.Â AbstrakDistribusi subtipe HIV-1 di Provinsi Kalimantan Barat dengan jumlah data yang memadai belum begitu diketahui, begitu juga subtipe yang dominant dan proporsinya. Tujuan analisis ialah untuk melihat distribusi subtipe HIV-1 yang beredar di Propinsi Kalimantan Barat dengan faktor risikonya. Data yang dianalisis berasal dari survei Genotipe virus HIV-1 di Provinsi Kalimantan Barat tahun 2010 pada kasus HIV atau AIDS dipilih purposif yang mengunjungi klinik Perawatan Sukarela dan Pengobatan (VCT) di Pontianak dan Singkawang. Untuk setiap kota dipilih 1 rumah sakit secara purposif. Spesimen darah diambil dari penderita untuk diperiksa dengan tes PCR dan sekuensing, kemudian data sosiodemografi dan riwayat penyakit dilakukan wawancara dengan kuesioner terstruktur setelah mendapat persetujuan dari penderita. Dari 80 spesimen serum yang diperiksa dengan PCR dan sekuensing didapatkan subtipe CRF01_AE sebesar 83,4%. Selain itu ditemukan subtipe E sebesar 10,4%, subtipe AC, A dan C masing-masing 2,1%. Proporsi terbanyak subtipe CRF01_AE ditemukan pada kelompok yang mempunyai status janda atau tidak menikah, kelompok dengan suku Melayu dan pada kelompok dengan usia 15- 30 tahun. Riwayat penularan terbanyak melalui IDU. Subtipe CRF01_AE HIV-1 merupakan subtipe rekombinan yang dominan beredar di Provinsi Kalimantan Barat.Kata Kunci: subtipe HIV-1, Kalimantan Barat.